2018
DOI: 10.1520/jte20170083
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Machinability, Microstructure, and Mechanical Properties of Al-7Si Alloy

Abstract: In this work, commercially available Al-7Si alloy was used, and the microstructure was modified by the additions of AlSr15, AlTi5B1, and Al3B. Cylindrical samples were cast into a sand mold and the machinability of the alloys was characterized by means of surface roughness, chip morphology, and buildup edge of the chips. Tool life and surface finish can be improved by decreased chip size by lowering the energy required for machining. The surface finish is an indicator of the quality of the material during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A twentyfold tool magazine allows changing the milling device, e.g., for roughing and finishing purposes, again not differing to industrial high-speed milling machines. Contrary to conventional milling processes, however, no cooling lubricant can be used as milling is performed within the powder bed, posing challenges such as, e.g., elevated temperature conditions or increased tool wear [ 28 , 29 , 30 , 31 ]. To access the tool wear properties in our study, we used previously determined milling parameters as given by Table 2 [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…A twentyfold tool magazine allows changing the milling device, e.g., for roughing and finishing purposes, again not differing to industrial high-speed milling machines. Contrary to conventional milling processes, however, no cooling lubricant can be used as milling is performed within the powder bed, posing challenges such as, e.g., elevated temperature conditions or increased tool wear [ 28 , 29 , 30 , 31 ]. To access the tool wear properties in our study, we used previously determined milling parameters as given by Table 2 [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have analyzed the significant correlation between microstructural parameters of solidification and machinability, however, although it is well-known how much the solidification process and the formed structures influence the machinability of the materials, there are few studies in the literature that do this analysis in nonferrous alloys [6,7]. Silva et al [8], when analyzing the correlation between shear temperature, tool wear and the microstructure in the columnar zone of an Al-7wt.%Si alloy, solidified in a horizontal directional system, observed that the maximum and average cutting temperatures increased and that the edge flank wear has decreased with increasing secondary dendritic arm spacing.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, transformation of coarse silicon particles to fine fibrous structure enhances the machinability of hypoeutectic Al−Si alloys by exhibiting the lowest BUE. 28…”
Section: Introductionmentioning
confidence: 99%
“…In fact, transformation of coarse silicon particles to fine fibrous structure enhances the machinability of hypoeutectic Al2Si alloys by exhibiting the lowest BUE. 28 The cutting force in machining Al2Si alloys also decreases at high cutting speeds. The reason can be attributed to the reduction of BUE at high cutting speeds.…”
Section: Introductionmentioning
confidence: 99%